evaluate the commutator [-d^2 / dx^2 , x] f (x) can anyone please check my work thanks. [-d^2 / dx^2 , x] f (x) = -2f '(x) -xf "(x) + -xf "(x) [-d^2 / dx^2 , x] f (x) = -2f '(x) = -2 (d/dx (f(x)) [-d^2 / dx^2 , x] = -2 d/dx
Follow Math Help Forum on Facebook and Google+
Originally Posted by myoplex11 evaluate the commutator [-d^2 / dx^2 , x] f (x) can anyone please check my work thanks. [-d^2 / dx^2 , x] f (x) = -2f '(x) -xf "(x) + -xf "(x) [-d^2 / dx^2 , x] f (x) = -2f '(x) = -2 (d/dx (f(x)) [-d^2 / dx^2 , x] = -2 d/dx There's a typo in the first line (the last term should be +xf''(x).) Otherwise it looks good. -Dan
View Tag Cloud